2003
DOI: 10.1177/15648265030244s209
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Trials of a Micronutrient Dietary Supplement in Schoolchildren and Pregnant Women in Tanzania

Abstract: Traditionally, the main strategies used to control micronutrient deficiencies have been food diversification, consumption of medicinal supplements, and food fortification. In Tanzania, we conducted efficacy trials using a dietary supplement as a fourth approach. These were randomized, double-blind, placebo-controlled efficacy trials conducted separately first in children and later in pregnant women. The dietary supplement was a powder used to prepare an orange-flavored beverage. In the school trial, children c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…Furthermore, two Vietnamese studies showed similar improvements in iron stores following ingestion of ironfortified fish sauce for six to 12 months [42, 43]. Comparable results were documented with dietary supplements containing iron and ironfortified milk [30, 31]. …”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, two Vietnamese studies showed similar improvements in iron stores following ingestion of ironfortified fish sauce for six to 12 months [42, 43]. Comparable results were documented with dietary supplements containing iron and ironfortified milk [30, 31]. …”
Section: Resultsmentioning
confidence: 98%
“…[21][22][23] A meta-analysis of multiple micronutrient supplementation showed a positive effect on child growth with effect sizes of 0.28 (95% confidence interval = 0.16-0.41) for height and 0.28 (95% confidence interval = -0.07 to 0.63) for weight. 24 Multiple micronutrient fortification showed a positive effect on growth in some studies 25,26 but not in other studies such as in school children in Thailand 27 and South Africa. 28 The present study investigated the impact of multi-micronutrient fortification in combination with de-worming in a school-based approach on growth, cognitive function, and parasite load among rural Vietnamese schoolchildren and whether combining the two interventions was more beneficial than either intervention alone.…”
Section: Introductionmentioning
confidence: 94%
“…Agricultural interventions by promoting production and use of vitamin A rich sweet potatoes significantly increased vitamin A intake from orange sweet potato sources and serum retinol levels 50,51 . Multiple micronutrient supplementation (MMN) among pregnant and lactating women significantly improved hemoglobin, serum ferritin, birth weight, small-for-gestational age (SGA), anemia in children with non-significant impact on serum retinol levels and preterm birth [52][53][54][55][56][57][58][59][60][61] . Malaria prevention in pregnancy showed that the use of ITNs in pregnancy sig- nificantly reduced the risk of peripheral parasitemia [62][63][64][65][66][67] .…”
Section: Findings From the Meta-analysismentioning
confidence: 99%